Antidiabetic effects of Peganum harmala seed extract on streptozotocin-induced diabetes in rats - Mozafar Khazaei; Mohamed Ali Mesgarof; Elham Ghanbari; Amir Hossein Khazaei (Avicenna Journal of Phytomedicine)
Objective: Diabetes, a chronic metabolic disease, has many complex complications and an increasing prevalence in various societies. Despite conventional drug treatments and limited surgical and tissue transplant methods, a definitive diabetes treatment remains to be found. Restoring damaged beta cells to insulin production or prompting other pancreatic cells to secrete insulin is an essential goal of diabetes research. The present study investigated the antidiabetic and regenerative effects of Peganum harmala seed extract (PHSE) on streptozotocin (STZ)-induced diabetes in rats.Materials and Methods: In this experimental in vivo study, male Wistar rats (200±10 g) were placed in 5 groups: control, untreated diabetic and diabetic groups treated with 100, 200, and 400 mg/kg doses of PHSE. Fasting blood sugar (FBS), C-peptide, insulin, and antioxidant parameters (total antioxidant capacity (TAC) and nitric oxide (NO)) of serum were measured. Pancreatic tissue was used for histologic staining and assessment of the expression of genes related to beta cell regeneration.Results: PHSE significantly improved FBS, weight loss, insulin, c-peptide, TAC, NO, and expression of pancreatic genes (insulin, PDX1 and neurogenin-3) (p<0.05). It also increased the number of pancreatic beta cells.Conclusion: PHSE has considerable regenerative and antidiabetic effects on changes caused by diabetes in rats’ serum and pancreas.